Comparative analysis of COVID-19 responses in Japan and Africa: diet, phytochemicals, vitamin D, and gut microbiota in reducing mortality—A systematic review and meta-analysis - Santa, Kazuki; Tamaki, Raita; Watanabe, Kenji; Nagaoka, Isao (Frontiers in Nutrition, 2024)
Background: As the novel coronavirus disease 2019 (COVID-19) pandemic subsides, the clinical sequelae are becoming more problematic. Interestingly, the statistical data indicate that Africa has experienced the lowest number of cases and deaths, with an unexpected phenomenon where the number of deaths from COVID-19 has not increased significantly. Several studies have investigated the relationship between diet and coronavirus. However, no systematic review/meta-analysis has conclusively linked diet (phytochemicals and vitamin D) and the gut microbiota in the context of COVID-19. Methods: This study examined the responses to COVID-19 in Japan and Africa, formulating the following hypotheses: 1) a healthy diet is effective against COVID-19, 2) blood vitamin D levels are associated with COVID-19 mortality, and 3) COVID-19 is associated with the gut microbiota. To investigate these hypotheses, a keyword search was conducted using PubMed, and each hypothesis was tested. Results: This study found that a healthy diet, particularly rich in phytochemicals such as polyphenols and flavonoids, is effective against COVID-19. An association was detected between blood vitamin D levels and COVID-19 mortality. The gut microbiota was linked to COVID-19 and its amelioration. These findings may have significant implications for not only understanding COVID-19 but also future prevention of pneumonia.